Sphenophorus levis Behavior Studies: Evaluating Insect Attractiveness or Repellency to One Insecticide Treatment and Assessing Nocturnal Insect Activity and Location Pattern - Urach Ferreira, Pedro Henrique [UNESP]; Ferreira, Marcelo da Costa [UNESP] (MDPI, 2023)
Sphenophorus levis Vaurie, 1978 (Coleoptera: Curculionidae). is a difficult to control pest in sugarcane that causes great damage to the subterranean part of the plant. Low insect control is the result of the pesticide application technology adopted but also a consequence of the lack of studies regarding the pest’s behavior. This research aimed to examine the attractiveness and repellency of one labelled insecticide dose to S. levis adults and to evaluate the activity and location behavior of S. levis adults under hourly observations over 24 h. Repellency and attractiveness studies were conducted in free-choice tests with treated soil with an insecticide product composed of lambda-cyhalothrin + thiamethoxam active ingredients and untreated soil. Insect activity and location behavior studies were assessed by conducting hourly observations of S. levis adults in containers with soil and sugarcane plant. The results indicate that S. levis adults are not repelled nor attracted to soil treated with the labelled dose of lambda-cyhalothrin + thiamethoxam in sugarcane. Additionally, insects presented nocturnal behavior for most activities (walking, digging and mating) starting at 6:00 p.m. until 2:00 a.m. An average of 21% of insects were out of the soil at night while the majority, 79%, remained inside the soil. During the day, most insects, 95%, remained hidden in the soil. Exposed insects were primarily located on the soil surface. According to these results, nocturnal insecticide applications may improve S. levis adult control due to greater insect activity and exposure at night.
Keywords: behavior; circadian rhythm; soil; sugarcane weevil